(untitled) (International Journal of Occupational Safety and Health, 2026)
Introduction: Healthcare professionals face irregular work schedules and sleep disruption. Identifying sleep–function phenotypes may support early prevention and occupational performance. Methods: Exploratory, cross-sectional study aimed to characterize sleep parameters and work-related conditions through certified sleep-specialist interviews, defining clinically meaningful sleep phenotypes in healthcare workers. This single-center cross-sectional study was conducted between December 2021 and February 2022 in a tertiary hospital. Interviews captured occupational and sleep-related parameters by a sleep specialist. Validated Greek versions of the Pittsburgh Sleep Quality Index (PSQI), Athens Insomnia Scale (AIS), and Epworth Sleepiness Scale (ESS) were administered. Data collection involved structured questionnaires and statistical analysis using STATA/IC software. Results: Among 38 healthcare professionals, most were medical/nursing staff (71%), one-quarter worked rotating shifts (26%), and the majority reported short sleep duration (74% <7 h). Unadjusted analyses indicated that poorer sleep was associated with younger age, reduced job performance, cognitive strain, morning headaches, and being overweight, whereas evening-type individuals reported fewer sleep complaints; in adjusted models, however, chronotype remained the only independent predictor of sleep disturbance, while reduced job performance independently predicted excessive daytime sleepiness. Medical/nursing personnel also reported higher rates of weight gain and greater daytime sleepiness compared with non-medical staff. Conclusion: This study demonstrates that clinician-led sleep interviews can effectively identify key sleep phenotypes in healthcare professionals, revealing that evening-type individuals consistently exhibit a more favorable sleep profile. Targeted screening of resilient sleep phenotypes, such as the evening type identified in this study, can help support safer and more sustainable working conditions for healthcare professionals.